Comparison of the pharmacokinetics of three concentrations of insulin aspart during continuous subcutaneous insulin infusion (CSII) in a pig model. (11th October 2012) - Petersen, Signe Beck; Nielsen, Flemming Seier; Ribel, Ulla; Sturis, Jeppe; Skyggebjerg, Ole
Abstract Objectives The aim of the study was to investigate the pharmacokinetic properties of insulin aspart (IAsp) in three different concentrations given as a continuous subcutaneous insulin infusion (CSII). Methods A randomized cross‐over study was performed in pigs, where IAsp U200, U100 or U20 was given for 8 h with the same total dose. Six pigs were included and blood was sampled during the CSII and 3 h after. Key findings The half‐life (t1/2) was 24.3 (range 17.3–41.3), 28.8 (range 19.6–54.3) and 23.6 (range 17.4–36.8) min for U200, U100 and U20, respectively. The area under the curve per dose (AUC/D) was determined to be 51.2 ± 19.5, 52.3 ± 12.5 and 51.6 ± 6.7 pm × min/kg for U200, U100 and U20, respectively. The steady state plasma concentration (Css) was 57.5 ± 27.1, 54.3 ± 10.3 and 55.1 ± 8.0 pm (mean ± SD) for U200, U100 and U20, respectively. Time to steady state (Tss) was 110 ± 36, 98 ± 48 and 90 ± 27 min for U200, U100 and U20, respectively. Conclusions In conclusion, no significant difference was found in t1/2, AUC/D, Css or Tss between the three IAsp concentrations when given at a basal rate in CSII.